Inculcation of Religion, Pancasila, and Local Wisdom as Foundations Building National Character - Putu Ronny Angga Mahendra (IAHN-TP Palangka Raya, 2022)
Character education has long been under pressure on informal education in Indonesia. During the first Jokowi administration, it was emphasized the importance of character education in the Nawacita program through PPK (Strengthening Character Education) with an emphasis on religious values, nationalism, fighting power, independence, cooperation, and honesty. In this character education, an educator must be able and able to explore the good values ??that already exist in the local culture of society, religious values, Pancasila as the basis and view of the life of the Indonesian nation. This will further expand, be more selective, better known, more explored so that students will be able to choose, recognize, understand, and live it in their lives.